If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2u + 3 = -11 Reorder the terms: 3 + 2u = -11 Solving 3 + 2u = -11 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2u = -11 + -3 Combine like terms: 3 + -3 = 0 0 + 2u = -11 + -3 2u = -11 + -3 Combine like terms: -11 + -3 = -14 2u = -14 Divide each side by '2'. u = -7 Simplifying u = -7
| 0.5(x+12)=4x-1 | | X^2+y^2-3x=0 | | 3x=20-5 | | 3v-17=3(v-8) | | 4(-7x+5)-3x=-5(3-x) | | 2(5c-1)-2=8c+4 | | -3a+2(a-5)=5(a-2) | | 2(3-X)=36 | | 9x+25=31-3x | | 6(3+n)=5n+3(1+2n) | | -7(t-1)=49 | | 7c-5c+2c-4=28 | | (2x+15)=x | | Y=4tan^6x | | 9n-47n+17n+-25n+47n-15=23 | | 3x^2+y^2+18x-2y-8=0 | | -5x^2=34x-7 | | y-(-1)=-1(a-0) | | 15y=3x | | 4x^2-3=10x | | 8(1-2x)=7(2-2x) | | X+9=3(4x-4) | | -4x^2+15=7x | | 41d-28d+3d-15d-1=22 | | -6(3)-3-(-7)(-2)-3= | | -6t=-7t+8 | | X^2+4x-3ifx=2-8i | | 5=2-x | | 6x-11=9x+10 | | 5(1+7n)+3(-3n+8)=2n-8+1+6n | | 30a-2a-27a=20 | | -7g+6=-6g |